Scaling‐up evidence‐based obesity interventions: A systematic review assessing intervention adaptations and effectiveness and quantifying the scale‐up penalty. (13th March 2019) - McCrabb, Sam; Lane, Cassandra; Hall, Alix; Milat, Andrew; Bauman, Adrian; Sutherland, Rachel; Yoong, Serene; Wolfenden, Luke
Summary: Maximizing the benefits of investments in obesity research requires effective interventions to be adopted and disseminated broadly across populations (scaled‐up). However, interventions often need considerable adaptation to enable implementation at scale, a process that can reduce the effects of interventions. A systematic review was undertaken for trials that sought to deliver an obesity intervention to populations on a larger scale than a preceding randomized controlled trial (RCT) that established its efficacy. Ten scaled‐up obesity interventions (six prevention and four treatment) were included. All trials made adaptations to interventions as part of the scale‐up process, with mode of delivery adaptations being most common. A meta‐analysis of body mass index (BMI)/BMI z score (zBMI) from three prevention RCTs found no significant benefit of scaled‐up interventions relative to control (standardized mean difference [SMD] = 0.03; 95% CI, −0.09 to 0.15, P = 0.639 − I 2 = 0.0%). All four treatment interventions reported significant improvement on all measures of weight status. Pooled BMI/zBMI data from prevention trials found significantly lower effects among scaled‐up intervention trials than those reported in pre–scale‐up efficacy trials (SMD = −0.11; 95% CI, −0.20 to −0.02, P = 0.018 − I 2 = 0.0%). Across measures of weight status, physical activity/sedentary behaviour, and nutrition, the effects reported in scaled‐up interventions were typically 75% or less of the effects reported in pre–scale‐up efficacy trials. The findings underscore the challenge of scaling‐up obesity interventions.